Effectiveness of Virtual Reality On Level of Labour Pain Among Primigravida Women – A Randomized Prospective, Passive Control, Interventional Trial: Life Sciences-Nursing - R, Umamaheswari; M, Annie Annal; S, Lavanya; V, Poongodi (International Journal of Life Science and Pharma Research, 2023)
Childbirth is a natural process, and its pain is perceived as normal. Labor pain is a universal experience for women; it is a highly unpleasant sensation that cannot be shared with others. Virtual reality (VR) learning is a technology that allows the user to explore and manipulate computer-generated real or artificial three-dimensional (3D) multimedia sensory environments in real-time. It allows for a first-person active learning experience through different levels of immersion, that is, a perception of the digital world as real and the ability to interact with objects. The objectives were 1. To assess the level of labor pain among primigravid women admitted in the labor ward. 2.To evaluate the effectiveness of virtual reality on the level of labor pain among the primigravid women admitted to the labor ward. 3. To find out the association between the level of labor pain among the primigravid women with selected True experimental research design was adopted for the study. The population of the study was Primigravid women with labor pain. Totally 60 samples were selected by Random sampling technique (lottery method), 30 in each group. Group I (experimental) received the virtual reality technique, and group II (control) received routine care. Pre-test was done using a structured questionnaire and assessment of the level of pain perception by numerical pain rating scale. In the post-test, after giving the Virtual reality technique to group 1 level of labor pain was assessed with a numerical pain rating scale. The results revealed that in the pre-test, the majority of samples, 24(80%), had severe pain,5(16.7%) had moderate pain, and 1(3.3%) had the worst pain in both the experimental and control group. In posttest, the majority of sample in group I 24(80%) had moderate pain, 2(6.7%) had mild pain, 4(13.3%) had severe pain and in group II 3(10%) had moderate pain, 25(83.3%) had severe pain, 2(6.7%) had worst pain. In the pre-test, the experimental and control group's mean and standard deviation values were 7.4, 1.04, and 7.57, 1.22 respectively. In the post-test, the experimental and control group's mean and standard deviation values are 5.23,1.25 and 8.07,1.01, respectively. The obtained Wilcoxon signed ranks test value for experimental group 4.867 and p-value < 0.0001. The Study findings reveal that the virtual reality technique effectively reduced labor pain among primigravid women using a numerical pain scale score.